Recurrent steroid cell tumor not otherwise specified with elevated testosterone and prolactin concentrations and impaired glucose metabolism: a case report - Yuan Xu; Hong-Kai Shang (Journal of International Medical Research, 2023)
Steroid cell tumor not otherwise specified (SCT-NOS) is a rare type of sex cord-stromal tumor with malignant potential. A 19-year-old woman underwent laparoscopic bilateral cystectomy, and postoperative pathology showed bilateral ovarian SCT-NOS. She had recurrence of the right tumor 8 years after the surgery, with shortened menstrual cycles, elevated testosterone and prolactin concentrations, and impaired glucose metabolism. We performed a laparoscopic right salpingo-oophorectomy. Testosterone and prolactin concentrations rapidly decreased and returned to the normal range after surgery. Subsequently, she had regular menstrual cycles and good glycemic control. The findings in our case suggest that there is a possibility of late recurrence in SCT-NOS. Therefore, we suggest that the postoperative follow-up period should be 10 years for this condition.